Design column loudspeaker IV - 241870 Mastura Zakaria (Kuala Lumpur : UTM, 1994)
The prime design target of this project (column loudspeaker) is the naturalness of sound. This project tend to concentrate the sound energy into a beam, where the higher the frequency, the thinner the beam. Part of the audience which is outside the beam will received poor asound quality. Column loudspeaker is mainly used in sound-reinforcement system for speech. Its application are widely used in mosque, halls, auditorium and etc. The airm of this project is to design and build a ptototype of column loudspeaker which consists of four drivers using constant voltage techniques. the loudspeaker shall be of 40' vertical polar response and 150' horizontal polar response. The poser rating shall be at least 80W instead of using two transformer. In order to reduce the cost, all of the components should be available locally and easy to get. The design will iimplement two techniques which is used in the previous design, power tapering techniques and acoustic techniques. The design also used a constant voltage input to cope with the utilization of power tapering techniques.